Social media use for climate change campaign among Indonesian millennials - Zein, Muhammad Rifki Adinur; Fadillah, Kurnia Lucky; Febriani, Nadia; Nasrullah, Riki; Khang, Nguyen Tan (PRofesi Humas, 2024)
Background: Climate change has threatened humanity and brought about serious impacts for at least two decades. The terrible threat can be addressed through social media. Purpose: This study examined how Indonesian millennials use social media to discuss and advocate for climate change. Methods: It employed mixed methods to combine climate change data from scholarly sources and strategic communication strategies in social media campaigns. Results: The results indicated a predominant presence of millennials, particularly in the 20-29 age group, using Instagram as the primary platform for climate change discussions. Social media highlighted limited engagement with experts and concerns about misinformation and emphasized the vital role of celebrities and influencers in climate change campaigns on social media. Conclusion: The research suggested that social media platforms like Instagram and WhatsApp facilitate climate change discussions among Indonesian millennials. They enable tailored communication strategies and emphasize the potential for social media campaigns to influence a certain behavior. This research also emphasizes the need for a combined approach involving online and offline channels, better climate change education, and collaboration. Implications: The findings underscore the necessity for Indonesia’s climate change advocacy to integrate offline and online communication strategies that are tailored to individual preferences and enhance millennials’ understanding through targeted education and social media campaigns. Public figures may also be involved for broader impacts.